Kajian Posisi Shear Wall Pada Gedung Tidak Beraturan Dengan Analisis Riwayat Waktu Beban Gempa - Heru Nurcahyo; Reni Suryanita; Alex Kurniawandy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Irregularity of building structure often emerges due to the room configurations to meet the architectural requirements. In irregular building, eccentricity exists between its center of mass and its center of rotation. The eccentricity generates torsion, which usually leads to the placement of rigid structural elements to increase the rotational stiffness of the building structure. One of the options to increase the building structure stiffness is by placing shear walls in the building. This research aims to analyze the impact of structure irregularity to the eccentricity of building structure and the effectiveness of various shear wall configurations to resist earthquake load. Building to be analyzed is Aulia Hospital buildings with earthquake load time history. Modeling is done with the help of the finite element program. The model will be made to the building without shear wall, existing and modification. The modified model is a model with a different positioning of the existing shear wall based parameter eccentricity. The analysis produced fundamental period and maximum displacement of the building as output. The fundamental period was calculated equal to 3.102 second for the building without shear wall; 2.087 second for the existing building; 2.011 second for Modification 1 Building; and 1.756 second for Modification 2 Building. The maximum displacement in X direction was calculated equal to 246.01 mm for the building without shear wall; 114.1 mm for the existing building; 107.24 mm for Modification 1 Building; and 102.07 mm for Modification 2 Building. Whereas the maximum displacement in Y direction was calculated equal to 230.37 mm for the building without shear wall; 169.7 mm for the existing building; 156.5 mm for Modification 1 Building; and 97.7 mm for Modification 2 Building. Based on the analysis results, it can be concluded that Modification 2 is the most effective model to resist earthquake loading.Keywords: Shear wall, Irregular Building, Eccentricity, Displacement